English as a Foreign Language Learning from the Students' Mental Health Point of View - Sabrina , Andita Zahra; Fitri , Aprilia Anisa; Wijirahayu, Suciana (UICELL, 2023)
This study aims to see how individual factors (self-efficacy, belief, and motivation) play a role in the anxiety experienced by students in learning English. The survey used quantitative in approach and the instrument of data collection is a questionnaire. The respondents were the first semester students who are learning English at Public Heath in a private university in Jakarta by adopting purposive cluster sampling technique. The preliminary research showed that the variables self-efficacy, belief, and motivation related to the anxiety in learning English that was part of mental health. The students will be individuals who try to find learning English strategies that are suitable for themselves. Keywords: EFL learners, Anxiety, University student, Mental health, Language Learning Strategies